Pilot Study on Students in Islamic Boarding Schools to Measure the Reliability and Validity of The Self-Regulation Scale - Shonia Dwiasa Pangukir; Dyah Astorini Wulandari (Proceedings Series on Social Sciences & Humanities, 2021)
This study aims to conduct a trial to determine the validity and reliability of the self-regulation scale and determine what dimensions/aspects are considered capable of forming self-regulation variables. Validity and reliability tests are carried out to determine a measuring instrument’s level of accuracy and consistency. This self-regulation variable is measured by the seven dimensions of Miller & Brown (Neal & Carey, 2005), namely receiving, evaluating, triggering, searching, formulating, implementing, and assessing. Thirty-six students at Islamic boarding school X in Banyumas, Indonesia, were involved as participants. Analysis of the data used to measure validity using the corrected item-total correlation formula and reliability using Cronbach’s alpha, which was analyzed using SPSS version 25. The analysis results prove that from the seven dimensions of self-regulation, there are 25 valid items and have a reliability coefficient of 0.908. Thus, the self-regulation scale can be used for research.